Blood Pressure Measurement: Clinic, Home, Ambulatory, and Beyond - Drawz, Paul E. (2012)
Blood pressure has traditionally been measured in the clinic setting using the auscultory method and a mercury sphygmomanometer. Technological advances have led to improvements in measuring clinic blood pressure and allowed for measuring blood pressures outside the clinic. This review outlines various methods for evaluating blood pressure and the clinical utility of each type of measurement. Home blood pressures and 24 hour ambulatory blood pressures have improved our ability to evaluate risk for target organ damage and hypertension related morbidity and mortality. Measuring home blood pressures may lead to more active participation in health care by patients and has the potential to improve blood pressure control. Ambulatory blood pressure monitoring enables the measuring nighttime blood pressures and diurnal changes, which may be the most accurate predictors of risk associated with elevated blood pressure. Additionally, reducing nighttime blood pressure is feasible and may be an important component of effective antihypertensive therapy. Finally, estimating central aortic pressures and pulse wave velocity are two of the newer methods for assessing blood pressure and hypertension related target organ damage.